Reducing Agency Problem Through Religious Values in Bhagavad Gita - Komang Ayu Trisna Dayanti; Ketut Sudarmini (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
This conceptual paper aims to provide a solution in reducing the agency problem through the implementation of religious values in Bhagavad Gita. The solution offered in this paper is cultivating religious values in the Bhagavad Gita, which includes: carrying out obligations by eliminating lust for the reward obtained, facing sorrow and joy with unanimous determination and eliminating ego. Implementation of these values will minimize the agency costs that may arise. Applying the religious values of the Bhagavad Gita can be a powerful step in reducing the agency problem. Furthermore, when one organization is able to implement it properly, it will become a role model for other organizations especially non-profit organizations. As far as the authors are concerned, there has been no published papers discussing how to reduce agency problem through religious values in Bhagavad Gita.